2018
DOI: 10.3390/min8060245
|View full text |Cite
|
Sign up to set email alerts
|

Selective Liberation of High-Phosphorous Oolitic Hematite Assisted by Microwave Processing and Acid Leaching

Abstract: The release of valuable minerals from the associated gangues is called liberation. Good liberation is essential to the subsequent separation stage. Selective liberation is advantageous to improve the degree of liberation. Oolitic hematite is one of the typical refractory iron ores in China, and its resources are abundant. However, owing to its fine dissemination and complex mineralogical texture, the conventional grinding processes are inefficient in improving the selective liberation of oolitic hematite. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…As a consequence, a lot of research efforts have been focused on phosphorus removal from high-phosphorus iron ore [20,24,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] in a bid to reduce the P content to acceptable levels. Processes that had been employed for phosphorus removal from iron ores include thermal treatment [7,21,24,[38][39][40][41][49][50][51][52][53], microwave treatment [38,[54][55][56], ultrasonic treatment [54], acid leaching [12,17,20,49,[56][57][58][59][60], alkaline leaching [5,59], bioleaching [30,[61]…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, a lot of research efforts have been focused on phosphorus removal from high-phosphorus iron ore [20,24,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] in a bid to reduce the P content to acceptable levels. Processes that had been employed for phosphorus removal from iron ores include thermal treatment [7,21,24,[38][39][40][41][49][50][51][52][53], microwave treatment [38,[54][55][56], ultrasonic treatment [54], acid leaching [12,17,20,49,[56][57][58][59][60], alkaline leaching [5,59], bioleaching [30,[61]…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the microwave treatment (f = 2Hz, pulse time = 100 µs, power = 5.6 kW, time = 30 s) of the samples (+9.2 −12.5 mm, 6 kg) prior to heap leaching (800 mL solution; 14 g/L sulphuric acid +3.75 g/L ferric sulphate, at 25 • C) improved the yield in the range of 7% to 12% [69]. Cai et al (2018) studied the combined effects of the microwave pretreatment, acid leaching, and magnetic separation of high phosphorus oolitic hematite (HPOH) [71]. The first phase of the study indicated that the microwave pretreatment (2.5 kW, 45 s, water quenched after treatment) of the representative HPOH samples reduced their work index from 15.25 kWh/t to 10.11 kWh/t.…”
Section: Downstream Benefits Economic Assessment and Industrial Applmentioning
confidence: 99%
“…Diversos são os processos empregados na remoção de fósforo de minérios de ferro, incluindo a separação por magnetização de torrefação (Cao et al 2018;, redução direta à base de carvão , tratamento térmico (Zhang et al 2018;, tratamento por micro-ondas (Cai et al 2018;Kim et al 2018), tratamento ultra-sônico (He et al 2018), lixiviação ácida (Xiang et al 2018;Cai et al 2018), lixiviação alcalina (Guo et al 2015;, aglomeração seletiva (Yang et al 2018), e flotação (Tudu et al 2018;.…”
Section: Introductionunclassified